Road traffic crash risk associated with benzodiazepine and z‐hypnotic use after implementation of a colour‐graded pictogram: a responsibility study. (9th September 2016) - Orriols, Ludivine; Luxcey, Audrey; Contrand, Benjamin; Gadegbeku, Blandine; Delorme, Bernard; Tricotel, Aurore; Moore, Nicholas; Salmi, Louis‐Rachid; Lagarde, Emmanuel
Abstract : Aims: To assess potential change in medicine exposure and association with the risk of road traffic crash across a time period that started before the implementation of a grading system warning of the effect of medicine on driving performance. Methods: Data from three French national databases were extracted and matched: the national health care insurance database, police reports and the national police database of injurious crashes. Drivers involved in such crashes in France, from July 2005 to December 2011 and identified by their national identifier, were included. Association with the risk of crash was estimated using a case–control analysis comparing benzodiazepine and z‐hypnotic use among drivers responsible or not responsible for the crash. Results: Totals of 69 353 responsible and 73 410 non‐responsible drivers involved in an injurious crash were included. Exposure to benzodiazepine anxiolytics was associated with an increased risk of being responsible for a road traffic crash during the pre‐intervention period (OR = 1.42 [1.24–1.62]). The association disappeared in the post‐intervention period, but became significant again thereafter. The risk of being responsible for a crash increased in users of z‐hypnotics across the study period. Conclusions: Our results question the efficacy of the measures implemented to promote awareness about the effects of medicines on driving abilities. Prevention policies relating to the general driving population, but also to healthcare professionals, should be reviewed.